Intrinsic religiosity and purchase intention: The role of attitude and moral efficacy - Andi Suseno; Utik Bidayati; Purwoko Purwoko; Mahamadaree Waeno (Jurnal Fokus Manajemen Bisnis, 2024)
The diversity of products on the market today raises various kinds of consumer considerations when making purchases. Consumers will consider the basics they have before making a purchase. Factors that influence consumers before making a purchase come from internal and external consumers. In this study, consumer behavior analysis is seen based on internal factors such as intrinsic religiosity, attitude, and moral efficacy. This study analyzes the effect of intrinsic religiosity on purchase intention by mediating attitude and moral efficacy. This study examines the behavior of consumers of cosmetic products in Yogyakarta, Indonesia and obtained a sample of 92 respondents. The research data were analyzed using the Smart PLS 4.0 software to test validity, reliability, and bootstrapping. The results of the study proved intrinsic religiosity does not negatively affect purchase intention, intrinsic religiosity has no positive effect on attitude, intrinsic religiosity has a positive effect on moral efficacy, attitude negatively affects purchase intention, moral efficacy has no negative effect on purchase intention,  attitude does not mediate the influence of intrinsic religiosity on purchase intention, and moral efficacy did not mediate the effect of intrinsic religiosity on purchase intention.